Reintegrasi Sosial Perempuan Korban Perdagangan Manusia Di LKS Sakura Al Jamaan Bogor - Ahmad Zulfa Styabudi; Binahayati Rusyidi; Eva Nuriyah Hidayat (Publikasi Indonesia, 2022)
The phenomenon of human trafficking in Indonesia has become a serious problem. The majority of victims who are targeted for human trafficking in Indonesia are women with the aim of being employed as laborers or for sexual exploitation. Women are still considered weak by some in society, making them a vulnerable group to become victims of human trafficking. With the increasing number of cases of human trafficking, the Ministry of Social Affairs, the Ministry of PPPA, the Ministry of Health, and the Indonesian National Police are partnering with LKS Sakura Al Jamaan Bogor in an effort to provide services for women victims of human trafficking. The stages that are carried out after the service delivery is considered complete are social reintegration. This study discusses a thorough understanding of the social reintegration of victims of human trafficking at LKS Sakura Al Jamaan Bogor. This research was conducted using descriptive qualitative methods to provide a thorough understanding of the topics discussed. The results of the study show that the implementation of social reintegration at LKS Sakura Al Jamaan Bogor adheres to the SOP of Permen PP and PA Number 8 of 2021, there are differences in the implementation of social reintegration during and before the pandemic, certain stages of implementing social reintegration, and there are opportunities and obstacles to implementing social reintegration at LKS Sakura Al Jamaan Bogor.